2023
DOI: 10.1001/jamaoncol.2023.2150
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Metronomic Oral Vinorelbine, Cyclophosphamide, and Capecitabine vs Weekly Intravenous Paclitaxel in Patients With Estrogen Receptor–Positive, ERBB2-Negative Metastatic Breast Cancer

Abstract: ImportanceIn spite of the effectiveness of endocrine therapy plus cyclin-dependent kinase (CDK) 4/6 inhibitors as the first-line treatment for estrogen receptor (ER)-positive, erb-b2 receptor tyrosine kinase 2 (ERBB2 [formerly HER2/neu])-negative (ER+/ERBB2−) metastatic breast cancer (MBC), patients eventually develop resistance, and eventually most will receive chemotherapy. The METEORA-II trial compared a metronomic all-oral treatment with intravenous (IV) chemotherapy.ObjectiveTo compare the efficacy of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…The METEORA-II trial showed that compared with weekly intravenous paclitaxel chemotherapy, oral vinorelbine + cyclophosphamide + capecitabine metronomic chemotherapy signi cantly prolonged TTF and PFS, and had a higher disease control rate (Munzone et al 2023). The OS of the two groups was similar.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The METEORA-II trial showed that compared with weekly intravenous paclitaxel chemotherapy, oral vinorelbine + cyclophosphamide + capecitabine metronomic chemotherapy signi cantly prolonged TTF and PFS, and had a higher disease control rate (Munzone et al 2023). The OS of the two groups was similar.…”
Section: Discussionmentioning
confidence: 99%
“…Due to data availability and model assumptions, our economic model has some limitations. Firstly, the clinical data comes from the METEORA-II trial (Munzone et al 2023), where the majority of patients were from Italy and the proportion of Asians was small and unavailable, which may have a slight impact on our results. Due to the lack of research results on the health effects of breast cancer in different states in China, this limitation cannot be avoided at present.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The majority used all oral metronomic therapy and different intravenous schedule as comparator. The results of a phase III study (METEORA) were presented recently, demonstrating the superiority of metronomic chemotherapy VEC (vinorelbine, cyclophosphamide and capecitabine) over weekly paclitaxel in terms of PFS and time-to-treatment failure (TTF) endpoints [ 14 ]. The METEORA study has thus established the VEC regimen as a safe and active option of MCT for the first-line treatment of advanced BC.…”
Section: Discussionmentioning
confidence: 99%